Experimental studies of ammonia co-fuelled combustion for future internal combustion engines - Bowling, William (2024)
The demand for rapid global decarbonisation has driven the emergence of zero-carbon alternative fuels for internal combustion engines (ICE). In order for the hard-to-abate industries such as shipping and heavy duty to meet the stringent targets, a diverse range of alternative fuels must be employed. Ammonia, being a more effective carrier of hydrogen than liquid hydrogen on a volumetric basis, with established production and transportation infrastructure, is poised to hold a significant fraction of the future fuel share. Overcoming the challenges such as high toxicity, low burning velocity, and high ignition energy is crucial in enabling the uptake of the fuel. A key opportunity to improve the combustion characteristics of ammonia is to co-fuel with hydrogen, a high energy fuel able to be produced from ammonia. Increasing interest in ammonia as a fuel has resulted in a new wave of literature focused on the fundamentals of ammonia and ammonia-hydrogen combustion as well as limited applied engine studies. The focus of this research was to enhance understanding of utilising combustion promoters, particularly hydrogen, to enable ammonia as a fuel for ICEs. The conducted studies aimed to advance knowledge regarding the trade-offs associated with optimising combustion, performance, efficiency, and pollutant emissions in the context of ammonia co-fuelling. The first study consisted of the design and build of a novel optical constant volume combustion chamber and test-rig control circuit that enabled fundamental investigation into ammonia-hydrogen combustions within an engine-like environment. The chamber was successfully designed, hydro-statically tested, and validated to British Standards. Flame imaging and analysis techniques were derived to enable insights into flame structures. Subsequent benchmarking testing with methane-air flames revealed a good correlation with previous literature values. Alongside this, ammonia-hydrogen-air combustion testing provided further detail around buoyancy impacts and the development of cellularity within mixtures at pressure with between 20-30% mixtures showing clear influence from hydrogen. The test data produced from these studies will be used in future comparisons of advanced ignition systems such as turbulent jet ignition. The second study was a retrofit of a fully-instrumented modern diesel compression ignition (CI) engine to operate with gaseous ammonia co-fuelling with diesel and/or hydrogen. The upgrade was completed iteratively, with the first iteration providing key learning that was carried forward. The first iteration achieved low ammonia substitution ratios, 18% (energy basis), due to limitations from cylinder-to-cylinder fuelling imbalance, ammonia liquid within the line and engine control. Upgrading the original fuelling system and engine control unit provided a finer level of control of injection of all fuels. A substitution ratio of 90% (energy basis) ammonia was achieved at full load, 600 rpm. At lower loads, significantly higher diesel quantities was required to maintain effective combustion, indicating limitations for future transient engine operation, approaching stoichiometric air-fuel ratios was an influential factor in enabling high ammonia substitution ratios. Throughout testing high levels of ammonia slip (10,000 ppm) were observed indicating the clear need for advanced exhaust after-treatment and/or in-cylinder mitigation strategies in future work.